Biointerface Engineering with Nucleic Acid Materials for Biosensing Applications (Adv. Funct. Mater. 37/2022). (12th September 2022) - Shi, Shi; Chen, Jing; Wang, Xiwei; Xiao, Mingshu; Chandrasekaran, Arun Richard; Li, Li; Yi, Chengqing; Pei, Hao
Abstract : Biointerface Engineering In article number 2201069, Mingshu Xiao, Chengqing Yi, Hao Pei, and co‐workers focus on nucleic acid‐engineered bio‐interfaces (including nano‐surfaces, cell surfaces, and macroscopic surfaces) and their use in chemical and biological sensing. They review the current development in nucleic acid‐engineered bio‐interface‐based biosensors and how the rational design of such constructs leads to more efficient biosensing platforms.